Pengembangan Potensi Saluran Irigasi Untuk Wisata River Tubing Di Desa Tambakbaya Garawangi, Kuningan - Hendrayana, Yayan; Ismail, Agus Yadi; Herlina, Nina; Althaaf, Naufal; Maryam, Siti; Mawangi, Rindi; Ramadhan, Mohamad Fajri (Empowerment : Jurnal Pengabdian Masyarakat, 2022)
The potential of natural resources that have not been explored and the current COVID-19 outbreak has resulted in problems in Tambakbaya village, one of which is that many people have lost their jobs. The purpose of this community service activity is to provide counseling regarding the potential development of irrigation canals into river tubing tours. This activity was carried out in Tambakbaya village which involved several stakeholders who were then informed about the potential for water river tubing tourism and planning for potential development starting from goals, targets and marketing. The extension activities for the development of the potential of irrigation canals into river tubing tourism objects received a very good response from the stakeholders of Tambakbaya village, although they did not fully understand the management of the tourism objects to be developed.